2020
DOI: 10.3389/fonc.2020.607909
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Colon Cancer

Abstract: A higher incidence of colorectal cancer (CRC) is found in males compared to females. Young women (18–44 years) with CRC have a better survival outcome compared to men of the same age or compared to older women (over 50 years), indicating a global incidence of sexual dimorphism in CRC rates and survival. This suggests a protective role for the sex steroid hormone estrogen in CRC development. Key proliferative pathways in CRC tumorigenesis exhibit sexual dimorphism, which confer better survival in females throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 292 publications
(314 reference statements)
6
82
0
2
Order By: Relevance
“…6 However, because there are potential sex-based differences in nutrient metabolism 7 and CRC risk, 8 a study leveraging a more diverse population is needed to confirm these findings. Cohort studies 9,10 and reviews 8,11 have reported that, compared with men, women have a lower overall incidence of CRC but a higher risk of proximal colon cancer, which tends to be more advanced and less differentiated than distal colon cancer. 8,10,12 In addition, there are potential sex differences in the gut microbiome in response to diet.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, because there are potential sex-based differences in nutrient metabolism 7 and CRC risk, 8 a study leveraging a more diverse population is needed to confirm these findings. Cohort studies 9,10 and reviews 8,11 have reported that, compared with men, women have a lower overall incidence of CRC but a higher risk of proximal colon cancer, which tends to be more advanced and less differentiated than distal colon cancer. 8,10,12 In addition, there are potential sex differences in the gut microbiome in response to diet.…”
Section: Introductionmentioning
confidence: 99%
“…For both gastric and esophageal adenocarcinomas, behavioral risk factors, such as obesity or exposure to carcinogens like tobacco smoking, do not entirely explain the sex disparity in incidence seen across multiple populations [3][4][5], thus strongly suggesting sex differences in susceptibility and/or biology for this type of cancer. In fact, increasing evidence suggests a sexual dimorphism in cancer biology, and sex-biased molecular signatures have been observed across multiple tumor types [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study identified that multiple LysoPCs and LysoPEs were upregulated in female patients with RCC (stage I) only, suggesting that the higher level of lysophospholipids in women with RCC would promote fatty acid supply that is essential for cancer cell growth at early stages 21 . It has also been discussed that sex-specific estrogen regulation may inhibit CRC cell survival by suppressed triglyceride biosynthesis, a vital lipid marker related to CRC progression 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex-related differences in CRC prognosis have become increasingly important in cancer research 16,17 . Female patients have a higher prevalence of right-sided colon cancer (RCC), which is associated with poorer overall survival (OS) 18,19 .…”
Section: Introductionmentioning
confidence: 99%